Radiant Futures: Utopian Art as a Phenomenology of Home-Seeking - Jordan Huston (Text Matters)
This essay examines the imaginative potential of utopian art. Utopian art is more than a representation of a possible future, it calls upon our imaginations to pull us into the act of home-coming itself. Following Heidegger, we depart from the idea that phenomenology is concerned with the imagination as an essential part of being-human. This essay leans on insights from Fredric Jameson’s phenomenological exploration of potential futures via the imagination as the means through which we experience utopia in our daily lives. This theorization is grounded in an analysis of Susan Sontag’s novel In America as demonstrating the utopian curves of consciousness as it is experienced phenomenologically in lived time. This novel lends credence to the idea that one purpose (among many) of utopian thinking is to find dreams worth reaching for; and in this reaching we find ourselves coming-home.